Beyond the L-Strut: Redefining the Biomechanics of Rhinoplasty Using Topographic Optimization Modeling. - Glass, Graeme Ewan; Staruch, Robert M T; Ruston, Julia; East, Charles A; Tan, P J (Aesthetic Surgery Journal, 2019)
Rhinoplasty utilizes cartilage harvested from the nasal septum as autologous graft material. Traditional dogma espouses preservation of the "L-strut" of dorsal and caudal septum, which is less resistant to axial loading than virgin septum. Considering the 90° angle between dorsal and caudal limbs, the traditional L-strut also suffers from localized increases in internal stresses leading to premature septal "cracking," structural-scale deformation, or both. Deformation and failure of the L-strut leads to nasal deviation, saddle deformity, loss of tip support, or restriction of the nasal valve. The balance between cartilage yield and structural integrity is a topographical optimization problem. Guided by finite element (FE) modelling, recent efforts have yielded important modifications including the chamfering of right-angled corners to reduce stress concentrations and the preservation of a minimum width along the inferior portion of the caudal strut. However, all existing FE studies offer simplified assumptions to make the construct easier to model. This review article highlights advances in our understanding of septal engineering and identifies areas that require more work to further refine the balance between the competing interests of graft acquisition and the maintenance of nasal structural integrity.